Electric vehicle charging/discharging station (EVCDS)-I : DC/DC booster design - Yao, Fei (2011)
With the development of green technology, electric vehicles (EV) which can be charged by renewable energy systems such as photovoltaic (PV) system will gradually replace gas-driven vehicles in future. The project started from literature research of solar cell, photovoltaic (PV) panel, maximum power point tracking techniques (MPPT), and DC-DC converter. The report mainly describes the design and simulation of PV panel, DC-DC boost converter and MPPT control circuit. The various subsystems are simulated using MATLAB Simulink software. PV panel and DC-DC boost converter with PI controller are constructed to test their performance. The main part of the report would focus on the simulation of whole PV system, which is enhanced by a maximum power point tracker circuit to track and to ensure the panel operates at the maximum power point (MPP) under certain conditions.